Deliberation and Procedural Automation on a Two-Step Task for Rats - Hasz, Brendan M.; Redish, A. David (Frontiers in Integrative Neuroscience, 2018)
Current theories suggest that decision-making arises from multiple systems. Human studies dissociate model-based and model-free systems, while rodent studies dissociate deliberation and habit. However, the relationship between these constructs remains unresolved. We adapted for rats a two-step task which has been used to dissociate model based from model-free decisions in humans. We found that an uncertainty-based algorithm predicted rats' choices on the maze better than an algorithm with a constant weighting between systems, supporting theoretical work suggesting decision-making systems are more likely to be used when their valuation is less uncertain. We also found that path stereotypy, a measure of behavioral consistency associated with procedural learning, was correlated with model-free certainty, while vicarious trial and error, a deliberative behavior, was increased during model-free uncertainty.